2007
DOI: 10.1016/j.neuropharm.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gq protein in behavioral effects of the hallucinogenic drug 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane

Abstract: SUMMARYExtensive evidence suggests that 5-HT2 receptors may play a role in mental disorders including schizophrenia. In addition, several studies indicate that G q -coupled 5-HT 2A receptors are likely targets for the initiation of events leading to the hallucinogenic behavior elicited by lysergic acid diethylamide (LSD), (±)1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (DOI), and related drugs. However, 5-HT 2A receptors couple to other G proteins in addition to G q protein. To evaluate the role of the G q si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 31 publications
2
43
0
1
Order By: Relevance
“…Moreover, deletion of the G q gene results in the lack of DOI-induced head twitches (67). The complexity of 5-HT2AR signaling may help to explain the paradox of why structurally similar 5-HT2AR ligands differ in their hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, deletion of the G q gene results in the lack of DOI-induced head twitches (67). The complexity of 5-HT2AR signaling may help to explain the paradox of why structurally similar 5-HT2AR ligands differ in their hallucinogenic effects.…”
Section: Discussionmentioning
confidence: 99%
“…To date the relationship between hallucination and DOI-induced shaking behavior is not fully understood. A recent molecular study revealed a possible link of head shakes to hallucination (Garcia et al, 2007). If this link is confirmed to be the case, it suggests that head shaking behavior may reflect not only physical but also mental changes.…”
Section: Discussionmentioning
confidence: 98%
“…5HT2A receptor activation is coupled to several intracellular signaling pathways (reviewed in Halberstadt, 2015). G q -mediated signaling activates the inositol triphosphate-diacylglycerol pathway leading to activation of protein kinase C. Behavioral effects of DOI are attenuated in G q knockout mice (Garcia et al, 2007). Signaling through G i/o , leading to activation of Src and expression of the immediate early genes egr-1 and egr-2, may be necessary to produce hallucinogenic effects.…”
Section: Basic Biological Mechanisms Of Classic Hallucinogensmentioning
confidence: 99%